The Potential Anti-Tumor Extract Of Ocimum Basilicum Lamiaceae Towards Colorectal Cancer Via The Angiogenesis Mechanistic Pathway - Al Deeb, Ibrahim Deeb Tawfiq (2021)
Angiogenesis is a process of new blood vessel development which can be triggered by inflammation. Both processes play crucial role in colorectal cancer. Natural products that have high level of antioxidants are known to have anti-inflammatory and anti-angiogenic activity and hence could be useful to treat colon cancer. In this work present here, methanolic extracts of 19 plant species of lamiaceae family found in Saudi Arabia were screened for their anti-angiogenic activity to ascertain their potency towards colon cancer. Only six extracts inhibited neovascularization formation by 50% or more, namely Thymbra capitate (Arial part) (97.93±2.63%), Premna resinosa (Stem) (85.03±16.84%), Phlomis viscosa Poir (Arial part) (81.47±22.95%), Salvia samuelssonii (Arial part) (55.69±12.72%), Ocimum basilicum (Leaves) (54.55 ± 4.27%) and Ocimum basilicum (Arial part) (53.99 ± 8.75%). However, methanolic extract of Ocimum basilicum (OB) leaves shown the highest inhibition towards endothelial cells proliferation and migration among other extracts. (OB) leaves were extracted with 70% ethanol (OBL70) at 55 ⁰C, causing a 43% increase in the anti-angiogenic properties compared to methanolic extract. OBL70 was studied in vitro against endothelial cells proliferation, cytotoxicity, migration, invasion and capillary-like structures using MTT, colony formation, scratch, invasion and tube formation assays, respectively.